2013
DOI: 10.1037/a0031434
|View full text |Cite
|
Sign up to set email alerts
|

Police officer alcohol use and trauma symptoms: Associations with critical incidents, coping, and social stressors.

Abstract: American police officers, this study examines the relationship between critical incidents, negative coping, and social stressors, and officer problematic alcohol use and posttraumatic stress symptoms, controlling for demographics. Results from hierarchical OLS regressions indicate that critical incidents are positively associated with alcohol use and PTSD symptoms. Coping mediates the relationship between critical incident and alcohol use, and is both directly and indirectly associated with PTSD symptoms. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 42 publications
5
93
0
2
Order By: Relevance
“…The results of this study are also similar to those of other studies showing that coping mediates the relationship between stress exposure and longer term psychological sequelae like posttraumatic stress in general (e.g., Menard & Arter, 2013), and in the context of natural disasters in particular (e.g., Benight & Harper, 2002;Bosmans, Benight, Knaap, Winkel, & Velden, 2013;Bosmans & van der Velden, 2015).…”
Section: Coping and Maternal Stresssupporting
confidence: 80%
“…The results of this study are also similar to those of other studies showing that coping mediates the relationship between stress exposure and longer term psychological sequelae like posttraumatic stress in general (e.g., Menard & Arter, 2013), and in the context of natural disasters in particular (e.g., Benight & Harper, 2002;Bosmans, Benight, Knaap, Winkel, & Velden, 2013;Bosmans & van der Velden, 2015).…”
Section: Coping and Maternal Stresssupporting
confidence: 80%
“…To date, studies have not focussed on police officers as victims of hate crime. Rather, when researching police officers as victims, the literature has tended to focus on the equipment and training aspects of officer safety (Stokstad, 2000;White, 2014) and the post-incident stresses and traumas of policing (Anderson et al, 2002;Ménard and Arter, 2013).…”
Section: The Dirty Work Of Policingmentioning
confidence: 99%
“…Prior studies have shown a high prevalence of PTSD among police officers of 15-50% [16][17][18], higher PTSD severity [19], and higher comorbidity with AUD [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%